Peran Resiliensi Dalam Menghadapi Depresi dan Ide Bunuh Diri pada Remaja: Studi Kualitatif di Layanan Kesehatan Jiwa - Maryati, Maryati; Sukesi, Niken; Puspitasari, Emilia (LPPM Institut Pendidikan Nusantara Global, 2025)
Adolescents are a vulnerable group to depression and suicidal ideation; however, limited studies have explored the dynamic process of resilience as a protective mechanism from adolescents’ subjective perspectives within mental health care settings. This research gap highlights the need to understand how resilience is formed, interpreted, and functions in the psychological recovery of adolescents at risk of suicide. This study employed an interpretative phenomenological approach to explore the lived experiences of six adolescents diagnosed with depression and suicidal risk factors. Data were analyzed using Interpretative Phenomenological Analysis (IPA). Three interrelated themes emerged: (1) complex emotional experiences as triggers of psychological crisis, (2) the construction of resilience through self-acceptance and spirituality, and (3) social support as a catalyst for strengthening adaptability. The synthesis of these themes indicates that resilience is not a static trait but a dynamic meaning-making process that fosters hope amid psychological distress. This study contributes to the theoretical understanding of adolescent resilience by emphasizing the interplay between intrapersonal and contextual factors. It provides a conceptual foundation for developing meaning-centered and socially supported clinical interventions aimed at preventing depression and suicidal ideation among adolescents.